Language teachers as eco-activists: From talking the talk to walking the walk - Maley Alan (Journal of World Languages, 2022)
The climate crisis has received a great deal of attention of late, yet its root causes go back to the last century and beyond. Also going back many years have been efforts to address the roots of the climate crisis. These efforts include the work of language teachers to research, create, trial, and share materials and pedagogical strategies for educating and mobilizing teachers, students, and other stakeholders to address the beliefs and practices that have led our species to the precipice of irredeemable disaster. This article seeks to serve as an annotated repository of works and collective wisdom of the author and colleagues, both near and far, as to how language teaching can accomplish its joint tasks of both facilitating student enjoyment of and expertise in their languages, and at the same time engaging students in fulfilling their responsibility as citizens of their home country and the world, a responsibility that has only grown more urgent due to the climate crisis. This repository is the result of 50 years of research, not with blinded control groups and statistical analysis (valuable though those methods can be), but of naturalistic investigation. The repository divides into three sections: Inspiration, Information, and Implementation. Strategies and ways that teachers have found useful for growing their own and their students’ knowledge of the causes of and possible solutions to the climate crisis are considered. The article ends with a poem by the author which addresses the important question of the role of the teacher in the classroom and beyond.